All Days 2015
DOI: 10.2118/175204-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced ICD Application Alleviating Well Intervention Challenges

Abstract: The drilling strategy of North Kuwait has embraced in the last few years to get more reservoir contact to maximize oil recovery. Presently, the wells are drilled with high deviation angle to intersect multiple pay zones and drain the existing prospects. However, water coning and edge water breakthrough are challenging to achieve production longevity. Inflow Control Devices (ICD) is a proved tool in oil industry, which can delay the water encroachment by creating uniform drawdown across wellbore section. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The steady state simulator works to enhance the design of the completion and the selection of the downhole devices. Hence, since it is a static simulator, the wellbore hydraulics simulation is done at a single time step (Carvajal et al, 2013;Awad et al, 2015).…”
Section: Wellbore Simulationmentioning
confidence: 99%
“…The steady state simulator works to enhance the design of the completion and the selection of the downhole devices. Hence, since it is a static simulator, the wellbore hydraulics simulation is done at a single time step (Carvajal et al, 2013;Awad et al, 2015).…”
Section: Wellbore Simulationmentioning
confidence: 99%
“…effectively in order to improve production and net present value (NPV), otherwise the ICDs even would be overlooked. Awad et al (2015) showed a typical flow diagram that should be used in a proper modeling and designing of ICD. This is presented in Figure 3.…”
Section: Introductionmentioning
confidence: 99%